Comparison of the Prevalence of Metabolic Disease Between Two Types of Urbanization in China - Han, Bing; Chen, Yi; Cheng, Jing; Li, Qin; Zhu, Chunfang; Chen, Yingchao; Xia, Fangzhen; Wang, Ningjian; Lu, Yingli (Frontiers in Endocrinology, 2018)
Objective: China is experiencing the world's largest urbanization. There are two primary types of urbanization in China: rural-to-urban migration and in situ urbanization, represented by Zhejiang Shangyu (SY) and Jiangsu Nanjing (NJ), respectively. Our aim is to compare changes in the prevalence of metabolic disease between these two types of urbanization in China. Methods: This is a cross-sectional study derived from the SPECT-China 2014 study. This study includes subjects and metabolic parameters from SY and NJ. Furthermore, biochemical and anthropometric indexes were taken into consideration and compared between the areas of interest. Results: The prevalence rates of diabetes, prediabetes and healthy subjects were 6.5, 17.9, and 75.7% in SY and 16.0, 31.0, and 53.0% in NJ, respectively. Industrial and agricultural jobs accounted for 77.9% and 32.0% of employment in SY and NJ, respectively. Fasting plasma glucose (FPG) was higher in SY than in NJ; however, HbA1c was lower in SY than in NJ. There was a significant difference in nonalcoholic fatty liver disease (NAFLD) and healthy subjects between SY and NJ (P < 0.05). Significant differences were also found with respect to body mass index (BMI), waist circumference (WC) and hip circumference (HC) between these two locations (P < 0.001). Logistic regression analysis revealed that the prevalence of prediabetes, diabetes, overweight, obesity and dyslipidemia was higher in NJ than in SY. Conclusions:In situ urbanization has notably changed occupational distribution. The prevalence rates of diabetes, obesity, and NAFLD were increased in rapidly urbanized areas. Thus, more attention should be paid to rapidly urbanizing areas to reduce the prevalence of metabolic disease.